Assessment Management Academic Supervision in Improving Teacher End - Rima Huswatun; VIP Paramarta; Yuyun Yuniarsih; Kosasih; Farida Yulianti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Improving teacher quality is a key factor in enhancing the quality of vocational education. Academic supervision serves as a strategic instrument for the professional development of teachers; however, its effectiveness is largely determined by a structured and sustainable assessment management system. This study aims to analyze the management of academic supervision assessment in improving teacher quality at SMK Luhur Baladika Bandung Barat, to identify implementation constraints, and to formulate strengthening recommendations based on the CIPP evaluation model (Context, Input, Process, Product). The study employs a qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data analysis is conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of academic supervision is not yet supported by a systematic assessment management system; assessment instruments are not standardized, supervision frequency is limited, and supervision results have not been optimally utilized for teacher development. The integration of the CIPP model is proven to be a relevant comprehensive evaluation framework to improve planning, implementation, and utilization of supervision outcomes. This study recommends strengthening a structured, sustainable, and teacher-needs-based academic supervision assessment management system to enhance the professional and pedagogical quality of vocational school teachers.